2020
DOI: 10.3390/ijerph17228391
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Responses to a Training Cycle in Female Youth Rowers

Abstract: Heart rate variability (HRV) is a reputable estimate of cardiac autonomic function used across multiple athletic populations to document the cardiac autonomic responses to sport demands. However, there is a knowledge gap of HRV responses in female youth rowers. Thus, the purpose of this study was to measure HRV weekly, over a 15-week training period, covering pre-season and up to competition in youth female rowers, in order to understand the physiological response to long-term training and discern how fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Due to the remote nature of the HRV data collection we were unable to enforce a pre-reading stabilization period or seated position for HRV readings which may have an effect on resting HRV values (27,55). Additionally, the statistical analysis used in our previous investigations demonstrated that changes in HRV is an appropriate method in similar small populations (56). Finally, we did not control for the menstrual cycle phase in this study.…”
Section: Experimental Considerationsmentioning
confidence: 94%
“…Due to the remote nature of the HRV data collection we were unable to enforce a pre-reading stabilization period or seated position for HRV readings which may have an effect on resting HRV values (27,55). Additionally, the statistical analysis used in our previous investigations demonstrated that changes in HRV is an appropriate method in similar small populations (56). Finally, we did not control for the menstrual cycle phase in this study.…”
Section: Experimental Considerationsmentioning
confidence: 94%
“…We recently tested this convergence by asking cyclists to remotely complete six 40-km time trials, using their personal equipment, while tracking training load, heart rate variability, nutrition, and psychological makers ( 2 ). In addition, we used remote data collection to track competitive youth rowers’ response to long-haul travel ( 3 ) and from an applied perspective, their pretraining heart rate variability across a season ( 4 ). We find that it is essential to determine outcomes that 1 ) subjects can obtain without assistance from researchers, 2 ) subjects are familiar with, 3 ) can be obtained with equipment already possessed by the subjects or can easily be provided, and 4 ) are meaningful.…”
mentioning
confidence: 99%